Polylactic acid films incorporated with nanochitosan, nanocellulose, and Ajwain essential oil: Synthesis, characterizations, with in-vitro and in-vivo antimicrobial properties for infected wound healing - Negin Ehyaeirad; Nima Babolanimogadam; Masoomeh Dadkhah; Leila Rezaie Shirmard (Carbohydrate Polymer Technologies and Applications, 2024)
Nowadays developing wound dressing with higher antimicrobial properties which is accelerates healing, considered an emerging issue. In this study, we designed polylactic acid (PLA) films incorporated with different concentrations of nanochitosan (NCH), nanocellulose (CNC), and Trachyspermum ammi (Ajwain) essential oil (AEO) with in-vitro and in-vivo antimicrobial properties, for infected wound healing. In this study, AEO was extracted and the components were analyzed. The appearance, thickness, release of AEO, and the in-vitro antimicrobial properties of films were evaluated and the films with higher antimicrobial properties were used as dressing the wounds of rats. The mechanical properties of selected films with higher healing properties were analyzed. The results showed that thymol, P-cymene, and γ-terpinene were the main components of AEO. Also, all PLA films with AEO had antimicrobial properties, especially gram-positive bacteria. Finally, PLA films incorporated with 4 % NCH and 3 % AEO showed the highest antibacterial and wound healing properties. According to the results obtained in the tensile strength test, the PLA/NCH films had good strength and NCH improved the mechanical properties of the films. According to the results obtained in this study, the PLA films incorporated with NCH and AEO oil can be a suitable option for new wound dressings.